Hubungan Kepatuhan dan Riwayat Pengobatan Terhadap Keberhasilan PengobatanTuberkulosis Resistan Obat dengan paduan obat jangka pendek 9-11 bulan di Provinsi DKI Jakarta - Budi Setiawan; Tri Yunis Miko Wahyono; Dwi Oktavia (Journal of Mandalika Literature, 2024)
Treatment success rate of drug-resistant tuberculosis (DR-TB) remains a challenge in DKI Jakarta. It is necessary to control adherence and the presence of treatment history that can affect treatment success. . The implementation of short-term combined treatment is expected to reduce the risk of treatment dropout (LTFU) and increase treatment success rates in patients undergoing treatment for DR-TB in Indonesia.(Ministry of Health, 2020). This study used a retrospective cohort design to look at the relationship of adherence and history to treatment success. The results showed that adherent patients had a potential treatment success of 9.14 times compared to non-adherent patients (RR = 9.14 (95%CI: 5.50-15.20)), The relationship between treatment history and the success of 9-11 month short-term combined DR-TB treatment can be seen in bivariate analysis which gives the results of no treatment history with an RR of 1.06 (95%CI: 0.90 - 1.24) but not statistically significant (p = 0.48). In stratification and multivariate analysis, there was no interaction or potential confounding from other variables on the association between adherence and history with treatment success.